Biochemical and Nanotechnological Studies in Selected Seaweeds of Chennai Coast - Manju Chandraprabha. M.,Seenivasan. R,Indu. H, and Geetha.S (Journal of Applied Pharmaceutical Science)
Article entitled 'Biochemical and Nanotechnological Studies in Selected Seaweeds of Chennai Coast' by Manju Chandraprabha .M, Seenivasan .R, Indu .H, and Geetha .S (J App Pharm Sci. 2012; 2 (11): 100-107.) has been retracted, at the request of the Authors. The authors have decided to retract this article because of conflicts among the authors on the right to publish these results.